Postnatal women's breastfeeding beliefs, practices, and support during the COVID-19 pandemic: a cross-sectional comparative study across five countries - K. P. Coca; E. Y. Lee; L. Y. Chien; A. C. P. Souza; P. Kittikul; S. A. Hong; Y. S. Chang (BMC, 2022)
Abstract Background Women with COVID-19 experienced numerous concerns and doubts about the safety of breastfeeding their babies, and lack of support may have impacted breastfeeding practices. This study aims to compare breastfeeding beliefs, practices, and contact with healthcare professionals regarding the level of postnatal feeding support provided during the COVID-19 pandemic in Brazil, South Korea, Taiwan, Thailand, and the United Kingdom. Methods A multi-country cross-sectional study was conducted with postnatal women in five countries. Women up to six months postpartum were invited to complete an online survey concerning the transmission of preventative measures, beliefs toward breastfeeding, infant feeding practices in the last 24 hours and experiences of postnatal infant feeding support between July to November 2021. Bivariate and multivariate analyses were performed to identify the association. Results Of the 3,253 eligible responses received, 39.5% of children were aged between one and two months, but in Taiwan (36%) and South Korea (42.8%) they were between three and four months. The mean of the belief score was significantly different among countries (p < 0.0001). Women in Brazil and the UK had a higher rate of breastfeeding at the breast (90.7% and 85.4%, respectively) compared to the three Asian countries (p < 0.0001) while feeding with expressed breastmilk in Thailand (59.9%), Taiwan (52.6%), and South Korea (50.4%) was higher than the others (p < 0.0001). Brazil and UK mothers (mean = 16.0 and 14.5 respectively) had a higher mean score for belief toward breastfeeding during the COVID-19 than the others. These results are inversely associated with breastfeeding but positively related to formula feeding practice. Postnatal feeding support during the COVID-19 pandemic was mainly provided by healthcare professionals (67.1%) and peers / family through face-to-face personal contact (51.6%) in all countries. Conclusion Some differences were found in breastfeeding beliefs during the COVID-19 pandemic in Asian countries. A positive breastfeeding belief was associated with the practice of breastfeeding at the breast. Women from all countries received postpartum infant feeding support from health professionals and peers / family through personal contacts. Governments need to emphasize and disseminate the importance of breastfeeding safety, especially in Asian countries.